2016
DOI: 10.1167/16.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tDCS on task relevant and irrelevant perceptual learning of complex objects

Abstract: During perceptual learning the visual representations in the brain are altered, but these changes' causal role has not yet been fully characterized. We used transcranial direct current stimulation (tDCS) to investigate the role of higher visual regions in lateral occipital cortex (LO) in perceptual learning with complex objects. We also investigated whether object learning is dependent on the relevance of the objects for the learning task. Participants were trained in two tasks: object recognition using a back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 66 publications
(88 reference statements)
1
11
0
Order By: Relevance
“…For instance, a study that administered multiple sessions of tDCS to the left lateral occipital cortex during an object recognition task found that anodal tDCS improved perceptual learning (over 4 days) in healthy individuals. 47 However, in another study that used repeated stimulations, anodal tDCS applied to Oz impaired the overnight consolidation of learning on a visual contrast detection task. 48…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study that administered multiple sessions of tDCS to the left lateral occipital cortex during an object recognition task found that anodal tDCS improved perceptual learning (over 4 days) in healthy individuals. 47 However, in another study that used repeated stimulations, anodal tDCS applied to Oz impaired the overnight consolidation of learning on a visual contrast detection task. 48…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of evidence demonstrates training-induced improvements in the perception of relatively simple visual aspects, such as frequency discrimination (Fiorentini and Berardi, 1981), orientation discrimination (Aberg et al, 2009;Jeter et al, 2010) and feature discrimination (Amar-Halpert et al, 2017;Censor et al, 2006;Censor and Sagi, 2008;Karni and Sagi, 1993). Interestingly, similar learning curves have been reported with more complex objects (Baeck et al, 2012(Baeck et al, , 2014(Baeck et al, , 2016Furmanski and Engel, 2000;Van Meel et al, 2016). This so-called object learning involves improved recognition of objects after multiple days of training.…”
Section: Introductionmentioning
confidence: 77%
“…Note that the procedure of shortening stimulus duration as the SOA gets smaller in could arguably result in a situation in which challenges in recognition performance are due to reductions in perceived stimulus contrast in low-level visual areas. We cannot rule out this possibility, yet it is assuring that the same manipulation was used in previous studies that found correlations with object recognition performance in object-selective cortex (Grill-Spector et al, 2000) and causal effects after stimulation in lateral occipital cortex (Van Meel et al, 2016).…”
Section: Object Learning Taskmentioning
confidence: 95%
See 2 more Smart Citations